Genetic Variability for Early Growth Traits in Second Season Sunflower - Lamichhane, Jay Ram; Wojciechowski, Alexandre; Bourgeois, Clémentine; Debaeke, Philippe (Frontiers in Agronomy, 2022)
Sowing a second season crop following the harvest of a first crop (hereafter referred to as double cropping) is a practice that allows for temporal diversification of cropping systems to increase the efficiency of land use and yield per unit area while improving the ecosystem services. Sunflower is particularly suitable for double cropping, especially under the current context of Southern Europe. However, planting sunflower in double cropping may result in poor establishment as the crop is very demanding in terms of seedbed preparations. In addition, most sunflower varieties available to date belong to late maturity groups (MGs), which were bred for conventional cropping. Planting these varieties in double cropping may further exacerbate the risk of crop establishment failure. Here, we performed laboratory and growth chamber phenotyping of 11 hybrid oilseed sunflower varieties with contrasting MGs and assessed their field performance for two consecutive years (2020 and 2021). We measured the variables, such as seed germination, seedling emergence dynamics and final rates, and post-emergence damage, as these characteristics are important for a uniform and robust crop establishment. Under laboratory conditions, we found statistically significant effect of varieties on cardinal temperatures and water potential for germination. Under growth chamber conditions, the maximum heterotrophic growth of the hypocotyl was higher (i.e., 85 mm) compared to that of the radicle (i.e., 80 mm). The seedling mortality rates under soil aggregates ranged from 0 to 12%, depending on the size and spatial distribution of soil aggregates in the seedbed. Under field conditions, the final rates of seed germination ranged from 87 to 98% and from 99 to 100%, while those of the seedling emergence ranged from 58 to 87% and from 78 to 94%, in 2020 and 2021, respectively. The average final rates of postemergence damage ranged from 13 to 44% and from 3 to 18% in 2020 and 2021, respectively. Bird damage was the main cause of pre- and postemergence losses. We found that a good sunflower establishment in double cropping is possible in the southwestern conditions of France, provided that there is no water stress in the seedbed. An optimal seedbed moisture ensures a rapid crop emergence and limits pre-and postemergence damage due to birds, by reducing the duration of the crop establishment phase, which is highly vulnerable to bird damage.